THE DILEMMA OF DUAL OVERSIGHT BETWEEN THE KPK AND SOES IN HARMONIZING ACCOUNTABLE AND TRANSPARENT STATE CORPORATE GOVERNANCE - Amirullah Amirullah; Sri Rahayu; Afifulloh Afifulloh; Ayu Febi Febrianti; Mutmainnah Mutmainnah (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to analyze the dilemma of dual oversight between the Corruption Eradication Commission and State-Owned Enterprises within Indonesia’s positive legal framework. The core issue arises from overlapping authorities following the amendment of Law No. 19 of 2019 concerning the Corruption Eradication Commission, which created disharmony between public oversight functions and corporate autonomy. The research employs a normative juridical method with statutoryand conceptual approaches. The findings reveal that the intersection between the Corruption Eradication Commission Law and the State-Owned Enterprises Law has caused authority fragmentation and normative confusion in the state financial supervision system. This condition weakens Corruption Eradication Commission independence and increases the risk of impunity in state corporate management. The study recommends legal reform through the establishment of an integrated legal framework that strengthens inter-agency coordination and regulatory harmonization across sectors. In conclusion, aligning the legal frameworks governing Corruption Eradication Commission and State-Owned Enterprises oversight is essential to reinforce anti-corruption effectiveness and to realize a transparent, accountable, and equitable governance system for state enterprises.